2011
DOI: 10.1007/s00330-011-2219-y
|View full text |Cite
|
Sign up to set email alerts
|

European and North American lung cancer screening experience and implications for pulmonary nodule management

Abstract: The potential for low dose computed tomography (LDCT) to act as an effective tool in screening for lung cancer is currently the subject of several randomised control trials. It has recently been given prominence by interim results released by the North American National Lung Screening Trial (NLST). Several other trials assessing LDCT as a screening tool are currently underway in Europe, and are due to report their final results in the next few years. These include the NELSON, DLSCT, DANTE, ITALUNG, MILD and LU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Other large multicentre studies such as the European randomised lung cancer CT screening trial (EUCT) or the Dutch-Belgian randomised lung cancer multi-slice CT screening trial (NELSON) are currently ongoing [5,6]. Now many associations recommend lung cancer screening [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Other large multicentre studies such as the European randomised lung cancer CT screening trial (EUCT) or the Dutch-Belgian randomised lung cancer multi-slice CT screening trial (NELSON) are currently ongoing [5,6]. Now many associations recommend lung cancer screening [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Also, inconsistent results were reported about dependency of volumetry variability on nodule size. Rampinelli et al [19] found that volumetry for larger nodules was more reproducible, based on 83 nodules with a mean volume of 2206241 mm 3 , yet Marchianò et al [28] observed that variability was not affected by nodule volume based on 233 nodules of 996127 mm 3 . In those in vivo studies, different volume ranges of included nodules have likely caused these inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we used five commercially available artificial spherical pulmonary nodules with a smooth surface in five diameters (3, 5, 8, 10 and 12 mm, corresponding to a volume of 14, 65, 268, 524 and 905 mm 3 ), made of polyurethane resin ( Figure 2). CT density was 1100 Hounsfield units (HU) at 120 kV.…”
Section: Phantommentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging plays a key role in patient care during all stages of the disease including diagnosis, staging, management, and assessing response to therapy [2,3]. More recently, a number of trials [4] including the National Lung Screening Trial (NLST) [5] have provided compelling evidence that in some populations, the mortality associated with lung cancer can be reduced by screening using low-dose CT (LDCT) [6], thus adding screening to the list of imaging roles.…”
Section: Introductionmentioning
confidence: 99%